Modeling the link between US inflation and output: the importance of the uncertainty channel - Christian Conrad; Menelaos Karanasos (University of Heidelberg, Department of Economics, 2010)
This paper employs an augmented version of the UECCC GARCH specification proposed in Conrad and Karanasos (2010) which allows for lagged in-mean effects, level effects as well as asymmetries in the conditional variances. In this unified framework we examine the twelve potential intertemporal relationships between inflation, growth and their respective uncertainties using US data. We find that high inflation is detrimental to output growth both directly and indirectly via the nominal uncertainty. Output growth boosts inflation but mainly indirectly through a reduction in real uncertainty. Our findings highlight that macroeconomic performance affects nominal and real uncertainty in many ways and that the bidirectional relation between inflation and growth works to a large extend indirectly via the uncertainty channel.
urn:nbn:de:bsz:16-opus-113115
Keywords: E31; C51; C32; 330; Bivariate GARCH process; volatility feedback; inflation uncertainty; output variability; Inflation; Risiko; Wirtschaftswachstum; Konjunktur; ARCH-Modell; Schätzung; USA